1996
DOI: 10.1093/carcin/17.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effects of genistein on estrogen receptor mediated pathways

Abstract: Genistein, a component of soy products, may play a role in the prevention of breast and prostate cancer. However, little is known about the molecular mechanisms involved. In the present study, we examined the effects of genistein on the estrogen receptor positive human breast cancer cell line MCF-7. We observed that genistein stimulated estrogen-responsive pS2 mRNA expression at concentrations as low as 10(-8) M and these effects can be inhibited by tamoxifen. We also showed that genistein competed with [3H]es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
254
2
11

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(287 citation statements)
references
References 11 publications
13
254
2
11
Order By: Relevance
“…30 -32 Dietary soy supplementation has been correlated with lower plasma estradiol concentrations 33,34 and soy phytoestrogens are known, among other actions, to compete with endogenous 17␤-estradiol for estrogen receptors. 35,36 Although the lung has not traditionally been considered a target for female hormones, 2 previous studies 7,37 both in Chinese women, have reported an increased risk of lung adenocarcinoma associated with shorter menstrual cycles, implicating hormones as possible factors. Reproductive events are known to modulate plasma estrogen levels; inverse associations have been demonstrated between estrogen levels and parity and age at first birth.…”
Section: Discussionmentioning
confidence: 99%
“…30 -32 Dietary soy supplementation has been correlated with lower plasma estradiol concentrations 33,34 and soy phytoestrogens are known, among other actions, to compete with endogenous 17␤-estradiol for estrogen receptors. 35,36 Although the lung has not traditionally been considered a target for female hormones, 2 previous studies 7,37 both in Chinese women, have reported an increased risk of lung adenocarcinoma associated with shorter menstrual cycles, implicating hormones as possible factors. Reproductive events are known to modulate plasma estrogen levels; inverse associations have been demonstrated between estrogen levels and parity and age at first birth.…”
Section: Discussionmentioning
confidence: 99%
“…Soy isoflavones also act independently of the ER: they exhibit anti-proliferative, anti-oxidant, and anti-inflammatory properties in vivo and in vitro (Guha et al, 2009). However, soy isoflavones exhibit only weak estrogenic activity: daidzein has 10-4 the activity per mole as 17β-estradiol (Wang et al, 1996;Santell et al, 1997). These anti-estrogenic effects by soy food intake may play a positive role in the better breast cancer outcomes (Shu et al, 2009;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The estrogenic activity of genistein and coumestrol in plants has also been established, although their beneficial effects such as preventing breast cancer have also attracted interest in these compounds [31,32]. Recently many persistent environmental chemicals including pesticides, plastic ingredients, and combustion by-products have been found to have estrogenic activity.…”
Section: Discussionmentioning
confidence: 99%